ACCOUNTANT—ATTORNEY COOPERATION. - Thurman, Sam D. (The Accounting Review, 1944)
Abstract The article presents information on accountant-attorney cooperation. In order to recognize an accounting problem and the consequent need to call in an accountant on a case, the author is of the view that every attorney and especially a tax attorney-should have some understanding of accounting principles. It is equally true that an attorney can best serve the interests of his client by having a sufficient understanding of the accounting problems involved in a case and being able to recognize the advantages to be gained from a proper audit or accounting. The converse of this situation is equally true. An accountant studies commercial law, not to enable him to practice law, but to give a knowledge of legal principles sufficient to prepare reports in such a way as to satisfy the legal duty of one's client to render an accounting and to enable the accountant to recognize the type of problem for which his client needs a lawyer. And the practice of law from the very first demonstrated the importance in modern life of cooperation between both professions. Every tax case involves both legal and accounting problems.